Glass transition and primary crystallization of Al86Ni6Y4.5Co2La1.5 metallic glass at heating rates spanning over six orders of magnitude. (15th March 2019) - Yang, Bin; Schmelzer, Jürn W.P.; Zhao, Bingge; Gao, Yulai; Schick, Christoph
Abstract: The glass transition and primary crystallization of melt-spun Al86 Ni6 Y4.5 Co2 La1.5 metallic glass have been investigated at continuous heating covering more than six orders of magnitude of heating rates. The heating rate dependence of the glass transition temperature is described by a generalization of the Bartenev-Ritland equation utilizing the Vogel-Fulcher-Tammann equation for the description of the viscosity and the Maxwellian relaxation time. This result is confirmed by measurements of primary crystallization performed also over a wide range of scanning rates. In the analysis a theoretical model is employed which takes into account the effect of decoupling of viscosity and diffusion. Graphical abstract: Figure Crystallization growth rate of the undercooled AlNiYCoLa liquid. Unlabelled Image